Kedudukan Tu’a Teno Gendang Curu terhadap Peralihan Hak Ulayat atas Tanah Lingko (Tanah Ulayat) menjadi Hak Privat - Hendrikus Andi Bagus; Sukardan Aloysius; Husni Kusuma Dinata (Hakim: Jurnal Ilmu Hukum dan Sosial, 2024)
The purpose of this research is to determine the position of Tu’a Teno Gendang Curu regarding the transition of indigenous land rights over Tanah Lingko (Customary Land) to private ownership and to understand the legal consequences of the transfer of indigenous land rights over Lingko (Customary Land) to private ownership. This study is an empirical legal research that employs an approach involving interviews as the primary source of data and literature review, including books, regulations, and other scholarly writings related to this research. The conclusions drawn from this research include, firstly, the division of Gendang Curu's Lingko marks the beginning of the transfer of rights over customary land. In a broader context, this division reflects customary legal actions in jointly managing land resources. However, in a more specific context, the division of Lingko also signifies the individual management of land for collective purposes, where the control over the managed land becomes an individual right. The transfer of customary rights is considered a preliminary step towards privatizing land rights, acknowledged by Gendang Curu's customary law through the sanctioned division of Lingko by Tu’a Teno. Secondly, the transfer of indigenous land rights over Lingko to private ownership by Tu’a Teno Gendang Curu weakens indigenous rights and strengthens individual rights. This opens up opportunities for various legal actions such as land transactions, donations, and inheritance, culminating in land registration to ensure legal certainty. However, the consequence of this process is the loss of Tu’a Teno's position and role as the manager of customary land. Tu’a Teno will only serve as a witness in case of land disputes.